Non-fluoric brightly colored glass cover with reduced temperature of burning - Рижова, Ольга Петрівна; Хохлов, Максим Андрійович; Кислична, Раїса Іванівна (Technology audit and production reserves, 2015)
The work featured research of influence of MnO2 on properties of frits and covers. It is established that even small quantity of output enamel MnO2 (0,1-0,4 mole %) introduced in composition instead of Fe2O3 facilitates improvement of fusibility and colorlessness of frit and improvement of optical and color characteristics of bright glass covers of red color. Optimal concentration of researched oxide MnO2 (0,2 mole %) in composition of enamel coatings is established. The brightly colored glass covers of red color with preset color characteristics are obtained: brightness (18-23 %), color pureness (45-55 %) and color tone (640-660 nm). Optical and color parameters of enamel coatings burnt under production conditions are somewhat lower. Thus, for example, color tone is mixed into purple area of visible spectrum that is not desirable. This can be explained by the durable burning of coatings and too high temperature of burning for this type of enamels reaching up to 850-860 ºС in some areas of furnace. That is, developed coatings require decrease of temperature and time of burning. Principal possibility of obtainment of non-fluoric brightly colored enamel coatings of red color by introduction of alloying additives Fe2O3 and MnO2 in determined concentrations in composition of researched enamel (per 0,2 mole %) is established as a result of research. The developed enamel glass covers with specified color parameters are more fusible and meet the requirements to external enamel coatings and can be recommended for testing under production conditions with low-temperature short-term mode of burning.